2022
DOI: 10.1007/s12029-022-00844-w
|View full text |Cite
|
Sign up to set email alerts
|

Using Telemedicine to Facilitate Patient Communication and Treatment Decision-Making Following Multidisciplinary Tumor Board Review for Patients with Hepatocellular Carcinoma

Abstract: Background and Aims A rapid increase in the use of telemedicine for delivering healthcare has occurred since the onset of the Covid-19 pandemic. There is evidence for using telemedicine to facilitate cancer care delivery for patients with hepatocellular carcinoma (HCC). Examining how telemedicine can be used to communicate multidisciplinary tumor board (MTB) recommendations for HCC has not been studied. This study has two specific aims: (1) to evaluate the patient perspective of the MTB review process and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…1) to optimize end-of-life care and avoid higher health care utilization with burdensome care transitions. [32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…1) to optimize end-of-life care and avoid higher health care utilization with burdensome care transitions. [32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a rapid increase in the use of telemedicine has occurred since the onset of the COVID-19 pandemic, with the continuous expansion of both access and coverage of its services [ 219 ]. Both European and American guidelines have already recommended the use of telemedicine to replace clinic visits, as well as replacing multidisciplinary team meetings to decrease the risk of the spread of COVID-19 [ 165 , 171 ].…”
Section: The Impact Of Covid-19 On Medical Personnel and Traineesmentioning
confidence: 99%
“…Both European and American guidelines have already recommended the use of telemedicine to replace clinic visits, as well as replacing multidisciplinary team meetings to decrease the risk of the spread of COVID-19 [ 165 , 171 ]. Moreover, it also allows overcoming barriers to access by reducing or eliminating travel distance, frequency, and associated costs, as testified by patients themselves [ 219 ]. Recent studies, for example, have shown that telemedicine may be an effective way to remotely evaluate HCC patients for liver transplantation [ 220 , 221 ].…”
Section: The Impact Of Covid-19 On Medical Personnel and Traineesmentioning
confidence: 99%
“…The American Joint Committee on Cancer (AJCC), TNM system assesses tumor size and invasion (T), lymph node involvement (N), and distant metastasis (M), with stages ranging from 0 (early) to IV (advanced), indicating cancer spread [8]. In stage III colon cancer, the malignancy penetrates the colon wall but does not affect nearby organs or distant locations, commonly involving lymph nodes [9]. Accurate staging guides treatment decisions and provides essential survival estimates, underscoring its pivotal role in managing stage III colon cancer [10].…”
Section: Introductionmentioning
confidence: 99%